Volume 2A: Turbomachinery 2019
DOI: 10.1115/gt2019-92073
|View full text |Cite
|
Sign up to set email alerts
|

Swirl Distortion Using Stream Vanes for Boundary Layer Ingestion Research

Abstract: The swirl distortion of a StreamVane™ was investigated in the NASA Glenn Research Center W8 test facility. The StreamVane™ was designed and generated by Virginia Tech based on CFD simulations and included a center body at the aerodynamic interface plane. The swirl pattern generated by the distortion was evaluated using a dense grid of 5-hole Pitot probe measurements captured using a rotating array of probes. Good agreement was found between the design intent and the results at 38.5 kg/s mass flow. The StreamVa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Other techniques for circumferential distortion panels are based on water cutting [141]. However, maybe the most complete and easy-to-implement is by 3D printing [112,113,120,139,140,146]. Some examples of distortion screens manufactured using these techniques are displayed in Fig.…”
Section: Methods Advantages Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other techniques for circumferential distortion panels are based on water cutting [141]. However, maybe the most complete and easy-to-implement is by 3D printing [112,113,120,139,140,146]. Some examples of distortion screens manufactured using these techniques are displayed in Fig.…”
Section: Methods Advantages Limitationsmentioning
confidence: 99%
“…In terms of when the modified velocity is settled downstream of the screen, Stephens et al [140] showed that, at distances of about one hydraulic diameter, the velocity field was already very similar to the final distribution achieved. Sivapragasam [141] conducted a more detailed investigation and determined that the pressure field and its gradients between two and five diameters downstream remained almost unchanged, whereas the variations were larger for shorter distances.…”
Section: Means To Condition the Flowfieldmentioning
confidence: 99%